1988
DOI: 10.1017/s1742758400009991
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Termites by Spodoptera littoralis Nuclear Polyhedrosis Virus

Abstract: A nuclear polyhedrosis virus isolated from the Egyptian cotton leafworm, Spodoptera littoralis, was found to infect termite castes of Kalotermes flavicollis. Laboratory studies indicated that no specific trend toward mortality responses among the different individuals of termites was noted. All test castes of termites, young, middle-sized, old and reproductive nymphs, and soldiers, were quite equal in their response to the virus infection, regardless of whether the virus concentration was high or low; a concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…So far, there have been very limited data on viruses capable of infecting termites (Al Fazairy and Hassan, 1988 ). It has been suggested that a virus infecting termites would be an ideal candidate for biological control (Chouvenc et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…So far, there have been very limited data on viruses capable of infecting termites (Al Fazairy and Hassan, 1988 ). It has been suggested that a virus infecting termites would be an ideal candidate for biological control (Chouvenc et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Batches of 20 or 40 larvae, depending on availability, were each exposed to two dose levels: a high dose of 106 PIBs per larva and a low dose of 103 PIBs per larva. The dose was administered by placing 1 [lI of virus suspension on either a small piece of the preferred food plant or a small diet plug in an individual chamber and allowing the larvae to feed for 24 h. Only those larvae which consumed the entire dose were removed onto clean foliage or diet. At this stage, one larva was removed from each dose and frozen to act as a virus-fed control for later probing.…”
Section: Methodsmentioning
confidence: 99%
“…Next, Nuclear Polyhedrosis Viruses (NPV) also can act as a biological control agent. This virus can infect the intestine of termite directly with virion as matrix protein called Polyhedral Inclusion Bodies (PIB) (Fazairy and Hassan, 1988). This virus is suggested as a good candidate for biological control of termites because it has the capability to complete its life cycle and spread, before the host dies (Sahayaraj, 2017).…”
Section: Discussionmentioning
confidence: 99%